MAIN OUTCOMES AFTER CARDIAC ARREST IN PREGNANCY: NARRATIVE REVIEW (Movimenta (ISSN 1984-4298), 2024)
Objective: To analyze the literature referring to the main outcome after cardiorespiratory arrest in pregnant women. Method: Narrative review in the Lilacs and Pubmed databases using the descriptors: “cardiac arrest”, “obstetric nursing” and “pregnancy” of publications between 2018 and 2022. The search took place from August to November 2022. Results: 10 were selected articles for analysis, where it was possible to consider that in cases of cardiorespiratory arrest during pregnancy, the recognition of maternal physiological changes, agility in initiating resuscitation maneuvers and perimortem cesarean section within 5 minutes, as well as the use of B-blockers were crucial to the denouement. Conclusion: However, the nursing team must work in an agile and synchronous way during the resuscitation management, aiming to clear the airways and guarantee the venous return for the success of the resuscitation.
Keywords: Cardiac Arrest; Obstetric Nursing; Pregnancy.; Cardiac Arrest. Obstetric Nursing. Pregnancy.